GLOBALISASI DAN IMPLIKASINYA TERHADAP PERUBAHAN STRUKSTUR SOSIAL MASYARAKAT DI SULAWESI SELATAN - Saifuddin Saifuddin (PREDESTINASI, 2024)
Globalization has greatly changed the social order and structure of a society or is it only still within the limits of a concept that continues to waver in every discourse on the progress of a particular community? This research aims to look at globalization and its implications for changes in social structure in South Sulawesi using a qualitative approach, case study type. Data was collected through in-depth interviews, limited observation and documentation. The data that has been obtained is then reduced, presented and summarized in a conclusion. Determining informants follows a purposive procedure, namely first determining a group of informants who will be used as data sources with certain criteria. The results of the research show that it is almost certain that there is no community that has not experienced change. Globalization is a real modernization term today, and is considered to have changed local thoughts in a region or country into global thoughts. Globalization has succeeded in entering the cultural, economic and political spaces of a community. Globalization brings new values that promise to make it easier to quickly penetrate the local values of a community. This means that the social structure of local society has been replaced by a new order, a globalized social structure. As a result of the impact of globalization, mutual cooperation and several traditions in marriage in South Sulawesi are starting to fade, and are no longer found. The process of spreading globalization in South Sulawesi through malls, CFC, McDonald's, Fizza Hut and most importantly through the digital world. Globalization in the sense of westernization is synonymous with lifestyle. In this context, capitalization, industrialization and bureaucratization play an important role in explaining changes in the social structure of a society.